An updated phylogeny and morphological study of the Phymaturus vociferator clade (Iguania: Liolaemidae) - Troncoso Palacios, Jaime (2018)
Species delimitation in Phymaturus has been a difficult task due to the highly conserved morphological and ecological features present in this genus. Almost all species of Phymaturus has been described without DNA data or lacking statistical analysis which makes even more difficult to compare species. Although two molecular phylogenetic studies have been recently published, here we provide the first multilocus phylogenetic reconstruction including all Chilean species, with samples from all type localities and some previously unsampled populations. We also estimate pairwise distances among the Chilean species of Phymaturus (P. vociferator and P. mallimaccii clades) and compare our results with the P. payuniae clade, where previous studies have used multiple lines of evidence. Additionally, we performed univariate and multivariate morphological analyses and skeletal comparisons (clavicle) for the species of the P. vociferator clade. As a result of this integrative approach, we describe a new species.